Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Kedai Kopi Kita Di Lampung - Naqiya, Alfina Zsazsa; Setyawan, Rai Rake; Adhilla, Fitroh (Universitas Hamzanwadi, 2023)
The purpose of this research is to ascertain if there is a significant relationship between customer satisfaction and product quality, service quality, and selling price. Google forms are used as part of the quantitative methodology employed in this investigation. The lame-show sampling method is being used to collect data from the target group, which consists entirely of paying customers. Multiple regression analysis was performed using the statistical package SPSS version 20 (Widyastuti & Nurfarida, 2019). Price has a positive and significant impact on customer satisfaction (with a sig. value of 0.003 0.05), as do product quality (with a sig. value of 0.000 0.05) and service quality (with a sig. value of 0.001 0.05), according to the study's findings. With a R squared value of 0.808, it can be concluded that the independent variables account for 80.8% of the variance in the dependent variable, while other factors account for the remaining 19.2%.